Advancing Metabolic Engineering of Saccharomyces cerevisiae Using the CRISPR/Cas System. Issue 9 (18th April 2018) - Lian, Jiazhang; HamediRad, Mohammad; Zhao, Huimin
Abstract : Thanks to its ease of use, modularity, and scalability, the clustered regularly interspaced short palindromic repeats (CRISPR) system has been increasingly used in the design and engineering of Saccharomyces cerevisiae, one of the most popular hosts for industrial biotechnology. This review summarizes the recent development of this disruptive technology for metabolic engineering applications, including CRISPR‐mediated gene knock‐out and knock‐in as well as transcriptional activation and interference. More importantly, multi‐functional CRISPR systems that combine both gain‐ and loss‐of‐function modulations for combinatorial metabolic engineering are highlighted. Abstract : The CRISPR/Cas system has been widely used to construct and optimize yeast cell factories to produce fuels and chemicals from renewable resources. In this review, the authors summarize CRISPR‐mediated genome editing (i.e., knock‐out and knock‐in) and transcriptional regulation (activation and interference). Multi‐functional CRISPR systems that combine gain‐ and loss‐of‐function modules are particularly highlighted.